2017
DOI: 10.3390/ijms18020264
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Cell Free Tumor DNA Detection as a Routine Tool forLung Cancer Patient Management

Abstract: Circulating tumoral DNA (ctDNA), commonly named “liquid biopsy”, has emerged as a new promising noninvasive tool to detect biomarker in several cancers including lung cancer. Applications involving molecular analysis of ctDNA in lung cancer have increased and encompass diagnosis, response to treatment, acquired resistance and prognosis prediction, while bypassing the problem of tumor heterogeneity. ctDNA may then help perform dynamic genetic surveillance in the era of precision medicine through indirect tumora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 116 publications
0
59
0
Order By: Relevance
“…This discrepancy may be attributable to several factors. Because pre‐analysis conditions undoubtedly play a crucial role, slight differences in plasma DNA extraction and quantification methods in each laboratory may affect the detection rate of ctDNA. Moreover, the detection rate could vary depending on the threshold setting …”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be attributable to several factors. Because pre‐analysis conditions undoubtedly play a crucial role, slight differences in plasma DNA extraction and quantification methods in each laboratory may affect the detection rate of ctDNA. Moreover, the detection rate could vary depending on the threshold setting …”
Section: Discussionmentioning
confidence: 99%
“…70 cfDNA/ctDNA are released in both apoptosis and necrosis of the cells at the interface of tumor and circulation, or active release. [71][72][73][74] Previously, it was believed that blood circulating nucleic acids were solely released by necrosis. However, Jahr et al reported that apoptosis plays a role in this process as well.…”
Section: Ctdna/cfdna: Physiological Characteristics and Analysismentioning
confidence: 99%
“…Hence, a blood sample is undoubtedly the more desirable alternative (Francis and Stein, 2015;Lowes et al, 2016). Furthermore, using this kind of methodology was successful in revealing pancreatic, lung, breast, and prostate cancer onset in patients but also melanomas in early-stage development through the cfDNA (Haber and Velculescu, 2014;Earl et al, 2015;Iwama et al, 2017;Oellerich et al, 2017;Takai and Yachida, 2016;Vendrell et al, 2017). Iwama and colleagues demonstrated that the use of dPCR in patients' liquid biopsy of lung adenocarcinoma was able to detect the EGFR "activating mutation" in cfDNA at a high rate of 81.3% and 100%, compared with Next Generation Sequencing (NGS) with 71.7 and 60.0%).…”
Section: Cell-free Dna (Cfdna) and Circulating Tumor Cellsmentioning
confidence: 99%